Elektrische Klangmaschinen Die Pionierzeit in Deutschland und Österreich - Donhauser, Peter (2007)
The publication deals with the time of pioneers in building "electrical musical instruments" in German speaking countries. It is based on a research project funded by the Austrian National Bank's "Jubilaeumsfonds" (project number 9382), where the popularisation of these instruments was in focus. Starting with the first attempts the development in the respective region is examined for the time between 1920 and 1945 using carefully investigated documents. After a short description of the roots going back to the 19th century the documentation continues with a critical evaluation of the constructions and their presentation in the 1920ties (especially Joerg Mager and Lev Termen and the reaction of experts and the public). Electro-optic and electromagnetic sound generation was invented in that time as well but appeared later on. There are examples for both principles in Austria and Germany reaching back to the 1920ties. A representative survey of press reports show the different estimations of the usability of electrical musical instruments by technicians, musicians and the public. The following decade is treated in several parts due to the political development in Germany. The first two years are mainly marked by the invention of the Trautonium, the Neo-Bechstein-piano, the Elektrochord and the Hellertion. This was the time when Berlin turned out as a centre for "electrical music", especially by activities of the "Rundfunkversuchsstelle" (radio research institute) at the University of Music and the Heinrich-Hertz-Institute. The first major public presentations at the Berlin Radio Shows took place in this time as well. After the year 1933 not only the political situation changed but the cultural preconditions for the usage of electrical instruments as well. The political convergence with the NS regime and the goodwill of the "ministry of public enlightenment and propaganda" played an important role. It turned out by the following development that the Trautonium, the electric organs by Vierling and the Hellertion by Bruno Helberger were used for official occasions. Vierling's "Grosstonorgel" was used during the Olympic games, on the other hand the development of Edwin Welte's light-tone organ was stopped for he was married with a Jewish woman. The work of Oskar Sala plays an important role in the area of conflict between technology, politics and music. As no detailed documentation of the work of Joerg Mager (who claimed to be the leading person in electro-music research) is available till now, this will be discussed in a separate chapter. A short description of the consequences after 1945 is followed by a detailed appendix: data of concerts, sound recordings, technical documentations and more than 600 patents. The book is based on extensive and original material, as it turned out by studying of secondary literature that many details are based on not provable sources. The facts are carefully documented using footnotes, the book is meant as a fundamental collection of sources for further scientific research.